More Jump More Health: Vertical Jumping Learning of Chinese Children and Health Promotion - Liu, Liu; Xi, Luo; Yongshun, Wang; Ziping, Zhu; Chunyin, Ma; Peifu, Qin (Frontiers in Psychiatry, 2022)
Vertical jumping is the most important of the fundamental motor skills, and has an important impact on children’s health. A systematic study was conducted on the influence of vertical jumping on children’s health and motor development patterns. In this study, the training and learning of vertical jumping was found to be effective in promoting children’s development, especially in terms of height and muscle growth. Training interventions were used to determine the influence of age on children’s learning of the correct vertical jumping motor pattern. Sex was found to have no influence on children’s learning of vertical jumping. Although children were found to be able to learn the correct vertical jumping motor pattern, they could not reach a level of proficiency and intuitively apply the acquired skills to task completion. Cognitive ability was found to have a crucial effect on motor learning among children, especially when they faced various task constraints.